Decifrando a origem de dubiofósseis do pensilvaniano da Bacia do Paraná, Brasil - Saldanha, João Pedro (Universidade do Vale do Rio dos Sinos, 2023)
Minerals are the fundamental record of abiotic processes and one of the main records of life over time, yet they do not have solid criteria that can distinguish biotic from abiotic products. This is because, more and more, the ubiquity of life on the Earth's surface has been proven and, therefore, we do not know all the biological roles in mineralization throughout the sedimentary cycle. Another reason is the natural condition of overlapping and repetition of geological processes that define the record. Mineral dubiofossils are relevant research points to resolve the issue since they are located on the boundary of knowledge between abiotic and biotic. Therefore, the objective of this dissertation is to decipher the origin and history of branched mineralized structures until then considered as mineral dubiofossils from the Rio do Sul Formation, Pennsylvanian of the Paraná Basin, Itaiópolis - SC, seeking to contribute to the investigation of the biogenicity of minerals. This occurrence is interesting because it refers to biological aspects, although it is difficult to associate it with any known fossil group and because of the context of overlapping geological processes that occur in rhythmites of Rio do Sul Fm., just very close to the contact of a sill of the Serra Geral Group – Lower Cretaceous with proven thermal effect, in a quarry exposed to the current weather. Based on investigations of previous dubiofossils, a description protocol was established in four attribute classes: 1) morphology, structure and texture, 2) relationship with the matrix, 3) composition, 4) context, also evaluating the indigeneity and syngenicity of the material and comparing with other biotic and abiotic minerals. The dubiofossil showed a high variation in shapes, sizes, textures, differences with the matrix, a complex organized composition of calcite with Fe, Mg, Al internally and an intricate context in which any of the multiple abiotic and biotic processes could have generated the occurrence. The extensive comparison with abiotic minerals, controlled, induced, and influenced biominerals did not result in any more probable hypothesis, excluding the possibility of being a controlled biomineral due to its diversity of morphologies without pattern and the purely thermometamorphic origin due to the branched elongated forms. Suggesting a complex history for the occurrence: syndepositional or eodiagenetic origin of some carbonate or sulfate (gypsum, ikaite, dolomite, calcite, siderite), which may be linked to the presence of microbial mats. EPS or filamentous bacteria may have served as a template for mineralization and may have also mediated mineral growth. Mesodiagenesis may have modified the occurrence, but the main agent was the Cretaceous intrusion which, by degrading the associated organic matter, dissolved, replaced the initial mineral, and precipitated calcite producing the dubiofossil. In all these steps, the physical-chemical and biological reactions, aided by the intrinsic characteristics of the matrix, amount of organic matter and distance from contact with the intrusive body, may have increased the morphological complexity. The material presented is an example that dubiofossils can be the result of a complex history and overlapping geological processes. Furthermore, it demonstrates the scarcity of biogenicity arguments that differentiate biominerals from abiotic minerals.
Keywords: Origem; Dubiofósseis minerais; Bacia do Paraná; Origin; Mineral dubiofossils; Paraná Basin; ACCNPQ::Ciências Exatas e da Terra::Geologia